Redesain Logo Band Regian Music dalam Upaya Meningkatkan Nilai Profesionalitas Visual - Deni Apriyanto; Suhadi Parman; Linda Norhan (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
Regian Music is a music service provider company established in 2021 and has been operating in the regions of Cirebon, Indramayu, Majalengka, and Kuningan, contributing to various events including parties. The Regian Music band has the potential to emphasize professionalism, but it faces challenges with its visual logo element. The current logo of Regian Music does not yet represent the band's vision and mission. In the old logo, there is inconsistency in the use of elements, typography, and colors. There is also a